Karakteristik Sifat Kimia Tanah Vertisol pada Lahan Sawah dan Tegalan di Kabupaten Jeneponto: Chemical Properties Characteristics of Vertisol Soil in Rice Fields and Dryland Fields in Jeneponto Regency - Raoda, Nur Aisyah; Ansar, Muh. (Jurnal Ecosolum, 2025)
Vertisol soil have high agricultural potential but are constrained by complex physical and chemical properties, thus requiring specific management strategies. This study aims to characterize the chemical properties of Vertisol soils under paddy field and dryland conditions in Jeneponto Regency and to relate them to crop productivity. The research method used was a survey with purposive soil sampling at three land-use type. Composite soil samples at a depth of 0–30 cm were analyzed in the laboratory to determine pH, organic C, total N, available P, available K, and CEC parameters. At te same thime production data were obtained through interviews. The results showed that farmers’ management practices were a more dominant factor in determining soil chemical properties than land-use systems. Organic C and total N contents tended to be higher in dryland (averaging 1.39% and 0.17%) than in paddy fields (averaging 0.71% and 0.18%). However the differences were not statistically significant based on the t-test (p > 0.05). Available P levels were very high in both land uses, indicating long-term fertilizer accumulation. Rice productivity in paddy fields (3.3–3.52 tons/ha/year) was identified as very low, which correlated directly with low organic matter content and nitrogen deficiency in the soil. Conclusion. It can be concluded that organic matter degradation resulting from management practices, such as straw removal, is the main limiting factor for rice productivity in Vertisol soils at the study site.